Literature Review Study of Lactational Massage on The Flow of Breast Milk - Yulianti, Indra; Yani, Lasiyati Yuswo; Arishinta, Chindytia Helma (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Lactation massage is a massage technique that can be worked out for smooth breastfeeding, by doing massages regularly as well as applying the correct breastfeeding technique. Lactation massage is useful for reducing pain, tension, stress, and anxiety, elevating mood or mood, increasing milk production, and encouraging loving maternal care, preparing the mother physically, emotionally, and mentally to face the postpartum period. This study aims to determine the relationship between lactation massage and the smoothness of breastfeeding in postpartum mothers. The method used in the preparation of this research is to use a literature review study approach by analyzing 16 articles that have been selected according to research criteria. The results from 16 literature review journals found that giving lactation massage is very effective for expediting breast milk. In this study it can be concluded that giving lactation massage can overcome the uneven production of breast milk, improve blood circulation, prevent breast milk from clogging, and make mothers more relaxed.